Penyalin Cahaya : Analysis of the Types of Sexual Harassment in Film - Fayidla Nurul Fikri; Keysha Shira Zafirah; Risma Siti Istikomah; Salsabila Zahra; Husnita Akhyar Hasibuan (Cinematology: Journal Anthology of Film and Television Studies, 2022)
hotocopier is a film released in 2021 and directed by Wregas Bhanuteja. This film is a mystery thriller drama genre that raises the issue of sexual violence which is considered sensitive and taboo among Indonesian people. The rise of sexual harassment cases in Indonesia encourages researchers to examine this. The Ministry of Education and Culture (Ministry of Education, Culture, Research, and Technology) explained that there are four classes of sexual harassment, namely: 1) verbal, 2) non-physical, 3) physical, and 4) online or through information and communication technology. Then, there are at least ten types of examples of sexual harassment other than rape. The method used in this research is descriptive qualitative. The researcher as a data collection instrument will conduct a literature study and a documentary study on the film Pengalin Cahaya in an effort to see the context of sexual harassment that appears in the show. From this study, it was found that the sexual harassment that occurred in this film was included in the category of physical sexual harassment. The perpetrators of sexual harassment in this film harass the opposite sex and same-sex partners who are partners in an organization on their campus. The perpetrators also cover up the crimes they have committed with the power they have. This proves the truth regarding research conducted in several countries that sexual harassment generally occurs in a place that is considered 'safe', where the sexual harassment that occurs in this film takes place on a campus where a place is considered 'safe' by the victim. As for the theory put forward by Fairchild and Rudhman (2008) regarding the organizational model approach, sexual harassment has a great chance if it is facilitated by power relations in a hierarchical structure. This theory is proven by the behavior carried out by the perpetrator of sexual harassment in this film, where he abuses the power and wealth of his parents to cover up crimes and silence the victim's mouth for his behavior.